Studying vocal-ventricular fold coupling using finite-element modeling - Yong, Wilson Weisheng (Nanyang Technological University, 2020)
Despite existing research establishing the influence of the ventricular folds on the vibration of the vocal folds, the ventricular folds continue to attract little research interest, particular in the realm of biomechanical simulation. This study documents the construction of a novel three-dimensional finite-element model of the vocal and ventricular folds capable of simulating their viscoelastic properties in fine detail. The model is used to validate the hypothetical effects of vocal-ventricular fold coupling (VVFC), and collision between the folds is shown to introduce damping and new modes of in the oscillation of the vocal folds. The results provide support against the open-closed continuum of glottis state, and instead show that interaction between parts of the epilarynx are necessary for a holistic account of phonation.